2018
DOI: 10.1016/j.jacc.2017.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Myocardial Remodeling Following Valve Replacement in Patients With Aortic Stenosis

Abstract: BackgroundLeft ventricular (LV) hypertrophy, a key process in human cardiac disease, results from cellular (hypertrophy) and extracellular matrix expansion (interstitial fibrosis).ObjectivesThis study sought to investigate whether human myocardial interstitial fibrosis in aortic stenosis (AS) is plastic and can regress.MethodsPatients with symptomatic, severe AS (n = 181; aortic valve area index 0.4 ± 0.1 cm2/m2) were assessed pre–aortic valve replacement (AVR) by echocardiography (AS severity, diastology), ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
185
2
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(228 citation statements)
references
References 48 publications
(65 reference statements)
10
185
2
14
Order By: Relevance
“…The presence of a normal LV mass with increased ECV, but apparently preserved cellular mass in our patients, could indicate a primary fibroblast activation rather than myocyte loss [30,31]. This is in contrast to a study on adult atrial switch corrected TGA individuals that showed increased ECV in the subpulmonary LV accompanied by decreased LV mass [25].…”
Section: Discussioncontrasting
confidence: 94%
“…The presence of a normal LV mass with increased ECV, but apparently preserved cellular mass in our patients, could indicate a primary fibroblast activation rather than myocyte loss [30,31]. This is in contrast to a study on adult atrial switch corrected TGA individuals that showed increased ECV in the subpulmonary LV accompanied by decreased LV mass [25].…”
Section: Discussioncontrasting
confidence: 94%
“…Therefore, an enhanced left‐ventricular filling does not automatically result in enhanced cardiac output, at least not within a few weeks. According to the findings of Treibel et al ., systolic function, after sAVR, is known to improve only after a period of 6 months to 1 year due to the regression of cellular hypotrophy that is accompanied by structural, functional and biomarker improvement (Treibel et al., ). Therefore, changes in systolic function after mini‐AVR are not likely to be observed this early after surgery in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, we speculate that the valve etiology profiles might have some effects on the mid-term outcomes even after removal of the diseased valve. Such differences in late complications among the three groups may possibly stem from the extent of postoperative regression of diffuse myocardial fibrosis and myocardial cellular hypertrophy based on the aortic valve etiology, as investigated in a recent study [26]. Recently, calcific/degenerative AS has been understood to be an active disease process akin to atherosclerosis from the perspectives of compelling histopathological and clinical data [27].…”
Section: Plos Onementioning
confidence: 99%